2017
DOI: 10.1139/as-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Paleolimnology of thermokarst lakes: a window into permafrost landscape evolution

Abstract: Widespread across northern permafrost landscapes, thermokarst ponds and lakes provide vital wildlife habitat and play a key role in biogeochemical processes. Stored in the sediments of these typically shallow and dynamic waterbodies are rich sources of paleoenvironmental information whose potential has not yet been fully exploited, likely because of concerns over stratigraphic preservation and challenges to develop reliable sediment core chronologies. Here, we present an overview of recently derived informativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 124 publications
(195 reference statements)
0
57
0
2
Order By: Relevance
“…Few studies have targeted thermokarst lakes over concerns that sediment mixing due to shallow depth and thermokarst processes obscures their sediment profiles. However, recent research suggests that informative paleoenvironmental records are preserved in these lake basins (Bouchard et al 2017). Even fewer studies have reported limnological or paleolimnological data for thermokarst lakes prior to and after drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have targeted thermokarst lakes over concerns that sediment mixing due to shallow depth and thermokarst processes obscures their sediment profiles. However, recent research suggests that informative paleoenvironmental records are preserved in these lake basins (Bouchard et al 2017). Even fewer studies have reported limnological or paleolimnological data for thermokarst lakes prior to and after drainage.…”
Section: Introductionmentioning
confidence: 99%
“…In general, thermokarst lakes in these regions primarily evolved throughout the Holocene with initiation peaks during the Pleistocene‐Holocene transition and the Holocene Thermal Maximum (Grosse et al, ; Romanovskii et al, ; Walter et al, ). They grow and coalesce but also drain partially or completely as a consequence of lake tapping, headward gully erosion, bank overtopping, coastal erosion, and anthropogenic disturbance (Bouchard et al, ; Grosse et al, ; Hinkel et al, ; Jones et al, ; Lenz, Grosse, et al, ; Marsh et al, ; Weller & Derksen, ). These partially or fully dewatered former lake depressions are called drained thermokarst lake basins (DTLBs; Hinkel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thermokarst lakes show distinct limnological and environmental properties depending on their ecoclimatic setting Roiha et al 2015;Deshpande et al 2016;Bouchard et al 2017). They are generally surrounded by peat deposits with sitespecific shoreline vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…They strongly influence primary production dynamics, nutrient cycling, carbon transport and processing, and oxygen concentrations (Smol and Stoermer 2010;Majewska et al 2012 and references therein). Diatom assemblages are used around the world as accurate bioindicators of environmental conditions (e.g., Lowe 1974;Smol and Stoermer 2010) and have been used successfully in numerous shallow-lake studies to evaluate climate-driven changes in aquatic environments (Bennion et al 2010;Lotter et al 2010;Bouchard et al 2017). Diatom-based paleoenvironmental reconstructions have been conducted in numerous sites across the circumpolar regions (Douglas et al 2004), from subarctic (Ponader et al 2002;Bouchard et al 2013;Rühland et al 2014) to high-Arctic Canada (Antoniades et al 2005;Ellis et al 2008;Douglas and Smol 2010) as well as in Siberia (Pestryakova et al 2012;Biskaborn et al 2013).…”
Section: Introductionmentioning
confidence: 99%